THE INFLUENCE OF COMPENSATION AND WORK-LIFE BALANCE ON EMPLOYEE LOYALTY INDOMARET LHOKSEUMAWE CITY - Juliyanti; Maisyura; Nur Faliza; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The high employee turnover rate at Indomaret Lhokseumawe is thought to be caused by dissatisfaction with the compensation system and lack of work-life balance. This study used a quantitative approach with a survey method, involving 43 active employees from several Indomaret outlets. The results show that compensation and work-life balance have a positive and significant effect on employee loyalty. This means that the better the compensation system and the more work-life balance employees feel, the higher their loyalty to the company. The implication is that Indomaret management needs to strengthen compensation strategies and work-life balance policies in order to create a healthy, productive work environment and be able to retain employees in the long term.